Controlled and Stabilized Light–Matter Interaction in Graphene: Plasmonic Film with Large‐Scale 10‐nm Lithography. Issue 11 (16th August 2016) - Hu, Yaowu; Kumar, Prashant; Xuan, Yi; Deng, Biwei; Qi, Minghao; Cheng, Gary J.
Abstract : Graphene–plasmonic metal nanostructures have great potential as optical metamaterials with strong light–matter interactions for applications in energy harvesting, biochemical sensing, and plasmonics. Currently, large‐scale fabrication of graphene–plasmonic hybrid systems have the following bottlenecks to realization of their full potential: 1) the geometry of metal nanostructures is not well controlled, 2) the substrates are rigid, and 3) low chemical and thermal stability of plasmonic metal nanostructures. Top‐down fabrication of a free‐standing hybrid film is demonstrated with graphene veiling for flexible‐substrate‐supported engineered plasmonic nanoarrays. Large‐scale graphene–plasmonic nanoengineered hybrid structures with the capability to generate large optical‐field enhancement, such as ultrasharp 3D pyramids, 10‐nm V‐grooves, and nanotrenches (10–100 nm), are nanoimprinted from physical‐vapor‐deposited nanocrystalline thin films on flexible substrates by laser‐shock‐induced 10‐nm lithography. Anisotropic light–matter interactions with tunable field enhancement, hot electron transfer at the graphene–metal interface, and optical reflectance in the graphene are shown in a sub‐100‐nm nanoengineered metal structure. The application of such hybrid films is demonstrated in trace‐level direct detection of antibiotics from their waste containers. This hybrid structure has excellent stability in a reactive environment (sulfur) and at elevated temperatures (ca. 300 °C). These 10‐nm lithography enabled graphene–plasmonic nanosystems will stimulate development of many novel devices in a hybrid, tunable hot‐carrier‐surface plasmonic concept. Abstract : Large‐scale graphene–plasmonics nanoengineered hybrid structures with the capability to generate large optical field enhancement are nanoimprinted from physical‐vapor‐deposited thin films on flexible substrates. In this structure, anisotropic light–matter interactions are demonstrated with tunable field enhancement, hot‐electron transfer at the graphene–metal interface, and optical reflectance. This hybrid structure also has excellent stability in reactive and elevated‐temperature environments.